Chemical profiling and evaluation of in-vitro antibacterial and antibiotic synergistic activities of Cleistanthus bracteosus Jabl. from Malaysian rainforests - Dassanayake, Mackingsley Kushan (2025)
Plants are rich and valuable sources of phytochemical constituents that can contribute to a variety of biological activities. The research in discovering novel antimicrobial compounds from plants has been of increased interest due to the global rise of antibiotic resistance. The present study aims to evaluate the in vitro antibacterial, antibiotic synergistic potential and the chemical profile of plant extracts associated with Cleistanthus bracteosus found in Malaysian rainforests. The antibacterial activity and synergistic antibacterial activity of chloroform, methanol and hexane crude extracts of C. bracteosus were determined against bacterial pathogens of Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Salmonella typhi and Acinetobacter baumannii. The chloroform stem extract exhibited the highest antibacterial activity which indicated a mean inhibition zone diameter (IZD) of 10 ± 0.26 mm at its highest concentration against the Gram-positive bacterium B. cereus. The best synergistic activity was shown for chloroform wood extract when combined with ampicillin against A. baumannii with a growth inhibitory index (GIIs) of 1.33. A fractional inhibitory concentration index (FICI) of f <0.5 was indicated for ampicillin and penicillin G when combined with chloroform stem, bark and wood extracts against A. baumannii. Potassium clavulanate profoundly synergized chloroform stem extract against E. coli ATCC 10536 (IZD = 27 ± 0.56 mm) and chloroform bark extract against S. typhi (IZD = 28 ± 0.54 mm). C. bracteosus extracts indicated the presence of secondary metabolites like flavonoids, phenols, tannins, alkaloids, coumarins, saponines and traces of terpenes. Chloroform extracts of bark, stem and wood consist of 20 bioactive phytochemical compounds according to gas chromatography-mass spectrometry analysis (GC-MS). Further analysis with high-performance liquid chromatography (HPLC) implied the presence of digoxigenin and lauric acid, existing as major compounds contributing to antibacterial and antibiotic synergism. Scanning electron microscopic (SEM) observations further elucidated the effects of C. bracteosus chloroform extracts on the morphology of susceptible organisms. The findings of this investigation justify that chloroform extracts of C. bracteosus can function as a novel antibacterial agent with synergistic potential.